Autophagy: A New Mechanism for Esketamine as a Depression Therapeutic. (21st August 2022) - Jiang, Guanghao; Wang, Yibo; Liu, Qingzhen; Gu, Tingting; Liu, Suting; Yin, Anqi; Zhang, Lidong
Graphical abstract: ESK reverses LPS-induced depression-like behavior by activating mTOR to inhibit autophagic impairments, while the mTOR inhibitor rapamycin opposes ESK. Highlights: ESK reverses LPS-induced depression-like behavior and alleviates both neuroinflammation and apoptosis. The inhibition of autophagy by activating the mTOR-BDNF pathway is an essential mechanism for the antidepressant effect of ESK. The combination of ESK with 3-MA did not enhance the antidepressant effect. Abstract: Depression is a serious physical and mental disease, with major depressive disorder (MDD) being a hard-to-treat, life-threatening form of the condition. Currently, esketamine (ESK) is used in the clinical treatment of MDD, but the drug mechanisms continue to be unclear. In this study, we explored the therapeutic efficacy of ESK against lipopolysaccharide (LPS)-induced neuroinflammatory, autophagic, and depressive symptoms and the possible mechanisms behind them. Our study demonstrated that LPS increased cytokine levels (TNF-α, IL-1β, IL-6), induced neuroinflammation, led to increased levels of autophagy markers, and enhanced autophagy activation, which ultimately caused depressive symptoms in mouse models. ESK inhibited autophagy via the mTOR-BDNF signaling pathway and significantly alleviated the adverse effects induced by LPS, mainly in the form of reduced levels of cytokines, apoptotic factors, and autophagic markers; elevated BDNF levels; and improved depression-like behavior. Furthermore, we were interested to know if ESK in combination with other autophagy inhibitors would have a better antidepressant effect, and we chose the autophagy inhibitor 3-MA for this attempt. Interestingly, the use of 3-MA did not attenuate or even enhance the therapeutic effect of ESK. The results suggest that, in the LPS-induced depression models, ESK conveyed an antidepressant effect via the inhibition of autophagy through the mTOR-BDNF pathway.